STRATEGI PRAKTEK PEMBELAJARAN KURIKULUM MERDEKA - Idhartono, Amelia Rizky; Lutfi Isni Badi’ah; Kaltsum Kamilah Khairunnisaa; Irene Balgis Salsabila (Universitas PGRI Adi Buana Surabaya, 2022)
The Merdeka Belajar curriculum is packaged simply and in-depth which is focused on the essential and development of student competencies according to the level of its phase. The characteristics of the Merdeka Belajar Curriculum include (1) project-based learning to develop soft skills and character in accordance with the profile of Pancasila Students, (2) focused on essential materials such as literacy and numeracy, and (3) flexible for teachers to carry out learning according to the abilities of students and make adjustments to local contexts and local content. In accordance with the rules of Law Number 20 of 2003 which states that the right of all Indonesian citizens to obtain education is no exception for children with special needs (ABK). Therefore, the Extraordinary School (SLB) also implements the Independent Learning Curriculum in accordance with the predetermined phases for students with special needs. By paying attention to the results of the analysis of these conditions, the PPM team of Special Education Lecturers provided training and assistance related to the implementation of the Merdeka Belajar Curriculum and focused on the practical strategy of the Merdeka Belajar Curriculum. The partner in this PPM activity is MGPK Special Assistance Teacher for Junior High Schools (SMP) in Surabaya. The problem faced by partners is the practical strategy implemented in the Merdeka Belajar Curriculum